Phytosterol Profiles, Genomes and Enzymes – An Overview - Darnet, Sylvain; Blary, Aurélien; Chevalier, Quentin; Schaller, Hubert (Frontiers in Plant Science, 2021)
The remarkable diversity of sterol biosynthetic capacities described in living organisms is enriched at a fast pace by a growing number of sequenced genomes. Whereas analytical chemistry has produced a wealth of sterol profiles of species in diverse taxonomic groups including seed and non-seed plants, algae, phytoplanktonic species and other unicellular eukaryotes, functional assays and validation of candidate genes unveils new enzymes and new pathways besides canonical biosynthetic schemes. An overview of the current landscape of sterol pathways in the tree of life is tentatively assembled in a series of sterolotypes that encompass major groups and provides also peculiar features of sterol profiles in bacteria, fungi, plants, and algae.